An ethical role model of our Amazon: Interview with José Manuyama Ahuite, environmental and intercultural activist from the Amazon - Guerra-Carreño, Zussel Mariella (2024)
From a detected ethical problem, appropriate ethical responses must arise. The extractive export model constitutes one of those ethical problems present in the Amazon, which is countered by the actions of upstanding individuals, ethical role models who awaken pathos and internalize the suffering of the land, the communities, and the planet. These everyday people show us another possible path—the path of Jesus, based on mercy and care, as the fundamental criterion that ethically defines the human being.